Complexity, Connections, and Soul-Work - Bloch, Deborah P. (Catholic Education: A Journal of Inquiry and Practice, 2008)
Organizational theory and personal behaviors are both shaped by contemporary thinking and theories regarding spirituality, history, and the order, shape and direction of modern culture. Complexity theory, discussed in this article, offers some helpful insights into appreciating the relationships and connections often overlooked in today’s fast-paced world.